Effect of Debudding on Growth and Tracheid Characters of Pinus caribaea Seedlings - Bhatnagar, H. P.; Talwar, K. K. (Indian Forester, 1977)
Debudding of terminal bud or axillary buds have resulted in variation in growth and tracheid characters of Pinua caribaea seedlings. Azillary debudding treatment has increased stem height and tracheid length, whereas, terminal debudding retarded stem height as well as tracheid length and tracheid lumen diameter. Both the debudding treatments have retarded stem diameter and fresh and dry weights of the seedlings.